In love : a memoir of love and loss - Bloom, Amy, 1953- (Random House, 2022)
"Amy and Brian's world was changed forever with his diagnosis of early onset Alzheimer's. Forced to confront the daily frustrations and realities of the disease and its impact on their lives and marriage, Brian resolved not to let it dictate his life and instead asked himself: What makes life meaningful, and how do I want to live the rest of mine? His decision led them to learn about Dignitas and to fly to Zürich for a peaceful ending of Brian's life. In Love is the illuminating story of a marriage, of the gradual awareness that something was deeply wrong, and of a disease's effect on a man, a woman, a family. What were the signs that Brian and Amy brushed aside, and how did they cope when they could no longer ignore the truth as confirmed by an MRI? Why, in retrospect, did Brian decide to retire from his architecture practice earlier than he had planned? Bloom goes on to recount their search for a dignified and kind solution to the pain of Brian's life, and their discovery of Dignitas in Zurich, where the choice for a dignified end of life can be realized. In this moving memoir, Bloom also writes of their life together before Alzheimer's, and of a love that runs so deep that they were willing to work to find a courageous way to part"--